Electric vehicle fluid testing / edited by Leonardo Israel Farfan Cabrera, Peter Lee, and Ali Erdemir. - Farfan-Cabrera, Leonardo I.; Lee, Peter (Engineer); Erdemir, A. (CRC Press, 2026)
The book explores developments, innovations, and discoveries in testing and analyses of fluids used in EVs in connection with tribological applications. It covers all major aspects of testing and evaluation of such fluids and provides readers with the most relevant information on the improvement of efficiency and durability of EV drivelines.